The Future Is Now: Preparing Sport Management Graduates in Times of Disruption and Change - Weese, W. James; El-Khoury, Michael; Brown, Graham; Weese, W. Zachary (Frontiers in Sports and Active Living, 2022)
COVID-19 disrupted the world, and the impacts have been experienced in many areas, including sport and higher education. Sport management academicians need to reflect on the past two years' experience, determine what worked and what did not work, and avoid the temptation of automatically returning to past practices. The authors of this manuscript applied the disruption literature and propose transformative changes in what sport management academicians teach (e.g., greater emphasis on innovation, entrepreneurship, automation, critical thinking skills to facilitate working in flexible environments and across areas), how colleagues teach (e.g., heightened integration of technology, blended learning models) and where colleagues teach (on-campus and distal delivery modes, asynchronous and synchronous delivery to students on campus and across regions/countries). Examples of start-up companies and entrepreneurial ventures are offered to help illustrate the changing sports landscape and the emerging opportunities for current and future students, graduates, and professors. Sport management professors are offered some suggestions to assist them in seizing this opportunity.